Relationship between nurses knowledge level and workload about implementation of patient identification - Arsyawina Arsyawina; Hilda Hilda; Supriadi Supriadi; Hesti Prawita Widiastuti; Annisa Syaputri; Joko Sapto Pramono (PAGEPress Publications, 2023)
Patient safety incidents can originate from patient identification errors. From the preliminary study, it was found that there were 3 cases of patient identification errors in the year 2022. The objective of this research was to determine the relationship between nurses knowledge level and workload with patient identification implementation. This study employed a quantitative method with a cross-sectional research design. This research aims to analyze the relationship between variables where the independent variable and dependent variable are identified at one unit of time. In this case, to determine the relationship between the level of knowledge and workload of nurses with the implementation of patient identification. The sample consisted of 93 individuals distributed across the inpatient wards. The research sample was selected used random sampling. The knowledge level and workload of nurses were independent variables, while the implementation of patient identification was the dependent variable. Data collected was used of a level of knowledge, workload, and application of identification questionnaire. Data analyzed used were with Chi-square test. The obtained p-value for the relationship between nurses knowledge level and the implementation of patient identification is p=0.018 (p<0.05). Therefore, there is a significant relationship between nurses knowledge level and the implementation of patient identification. P-value for the relationship between nurses workload and the implementation of patient identification is p=0.564 (p>0.05).  This explains that there is no significant relationship between nurses workload and the implementation of patient identification. There is a significant relationship between nurses knowledge level and the implementation of patient identification. The majority of nurses demonstrated a good implementation of patient identification. It is recommended for the hospital management to make efforts to improve nurses knowledge, especially in the area of patient safety.